Fraud Detection System For Rotor Pay Phone - Spian, Nurwardiah (2007)

(untitled)
Pay phone, also known as public telephone, is very vulnerable to fraudulent abuse. Rotor pay phone is determined as most prone set to fraud. TM Berhad estimates loses millions of ringgit each year due to fraudulent activities. To help in battling the growing worldwide problem of pay phone fraud, a fraud detection system was developed. The system is developed in order to cater many types of frauds, commonly happen to Rotor pay phone in Malaysia such as line tapping, line cutting, shorting and grounding fraud. It does not deteriote voice quality of pay telephone or introduces significant delay during normal pay phone operation such as dialing, conversation and metering signal. The system comprises of two sets of fraud detection modules; Anti Fraud Device 1 (AFD1) and Anti Fraud Device 2 (AFD2). AFD1 is installed inside pay phone set,whereas AFD2 is installed in TM exchange. The system is based on a signal exchange between AFD1 and AFD2. When the pay phone handset is off-hook, the AFD1 and AFD2 will communicate with each other to detect any fraud. As soon as fraud is detected, the line will be terminated by AFD2. The system has been tested successfully using TM Berhad line infrastructure. The results obtained shows the system can caters most of pay phones which are located in urban areas. This will help TM Berhad to greatly reduce loses due to fraud.